Description of Dental Caries Knowledge in Class IV, V and VI Students After Counseling Using Clap For Teeth Card Media (Study at UPT SDN 227, Gresik in 2025) - Iklimah, Riza May Fildzah Bilqis; Hidayati, Sri; Mahirawatie, Ida Chairanna (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
According to the Indonesian Health Survey (SKI) in 2023, the caries-free rate in Indonesia at the age of 10-14 years is 35.5%. problem statement : The low caries-free rate at UPT SD Negeri 227 Gresik is a serious dental health problem. Based on an initial examination of 15 students in grades IV-VI, 86.67% were diagnosed with caries, 13.33% of caries-free students were far below the national caries-free rate of 35.5%. This school also does not have an active UKS and UKGS program. Interventions through counseling and attractive educational media are needed to increase student awareness and behavior in caring for oral health. This study endeavors to understand description regarding tooth decay knowledge among students of grades IV, V, and VI after counseling using clap for teeth card media at UPT SD Negeri 227 Gresik in 2025. Method : The current study is descriptive, with 32 learners serving as the research participants in grades IV, V, and VI UPT SDN 227 Gresik. Data was collected through questionnaires. Using mean calculation analysis in percentages displayed in tables. Results : The research results show that knowledgeability about tooth decay definition is good, the knowledgeability about tooth decay causes is good, the knowledgeability about tooth decay prevention is good, the knowledgeability about tooth decay treatment is adequate, and the knowledgeability about tooth decay consequences is good. Conclusion : It is concluded that the understanding of tooth decay in the classes of grades four through six members at SDN 227 Gresik is rated as good.